Examining Undergraduate Computer Science Participation in North Carolina. - PAYTON, FAY COBB; BUSCH, ALEXA (Communications of the ACM, 2020)
The authors discuss the question of recruiting students for colleges' computer science programs. They mention the efforts made by North Carolina colleges to broaden participation, the emphasis on recruitment of minority college students, and trends in the completion of computer science programs as signified by conferred bachelor's degrees.